Weather data measured during ALKOR cruise AL575 on 2022-06-30 - Tim Weiß; Mark Schmidt; Matthias Haeckel (PANGAEA, 2025)
Weather data (atmospheric pressure, air temperature, humidity, wind direction and speed) were monitored during AL575 cruise on 2022-06-30 from the DWD weather station (EUropean Common Automated Weather Station, short EUCAWS) at about 23 m altitude and obtained via the WERUM dship repository (https://dship.geomar.de). The weather data was correlated to atmospheric methane and carbon dioxide measurements that are published separately at doi:10.1594/PANGAEA.982665 .
In: Weiß, T et al. (2025): Weather data measured during ALKOR cruise AL575, 29 June 2022 – 12 July 2022, Kiel – Kiel [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.983833